2020
DOI: 10.1093/cid/ciaa1298
|View full text |Cite
|
Sign up to set email alerts
|

A National Strategy to Diagnose Coronavirus Disease 2019–Associated Invasive Fungal Disease in the Intensive Care Unit

Abstract: Background Fungal co-infection is a recognised complication of respiratory virus infections, increasing morbidity and mortality, but can be readily treated if diagnosed early. An increasing number of small studies describing aspergillosis in COVID-19 patients with severe respiratory distress are being reported, but comprehensive data is lacking. The aim of this study was to determine the incidence, risk factors and impact of invasive fungal disease in adult COVID-19 patients with severe respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
431
2
18

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 371 publications
(505 citation statements)
references
References 26 publications
22
431
2
18
Order By: Relevance
“…Unfortunately, the diagnostic yield of serum galactomannan is low in CAPA as, at best, 20% of patients showed positive results, and proven CAPA cases have been reported with negative serum galacto mannan. 9,12 This low sensitivity is in line with published performance of serum galactomannan detection in non-neutropenic patients in ICUs but lower than the 65% sensitivity of serum galactomannan in patients with IAPA. Overall, serum galactomannan has decreased value for excluding CAPA.…”
Section: Mycological Evidencesupporting
confidence: 78%
See 4 more Smart Citations
“…Unfortunately, the diagnostic yield of serum galactomannan is low in CAPA as, at best, 20% of patients showed positive results, and proven CAPA cases have been reported with negative serum galacto mannan. 9,12 This low sensitivity is in line with published performance of serum galactomannan detection in non-neutropenic patients in ICUs but lower than the 65% sensitivity of serum galactomannan in patients with IAPA. Overall, serum galactomannan has decreased value for excluding CAPA.…”
Section: Mycological Evidencesupporting
confidence: 78%
“…IPA is emerging as a serious secondary infection in patients with COVID-19 and ARDS, and two studies have indicated excess mortality rates of 16% and 25% compared with patients without evidence for aspergillosis. 11,12 These excess mortality rates are similar to that found for patients with IAPA, in whom the survival rate in intensive care units (ICUs) was 24% lower than in patients without this secondary infection. 1 CAPA diagnosis was associated with ICU mortality in a logistic regression model, even after adjustment for age, need for renal replacement therapy, and sequential organ failure assessment score at ICU admission.…”
Section: Capa Characteristics and Host Factorssupporting
confidence: 63%
See 3 more Smart Citations